Pengaruh Motivasi, Lingkungan Kerja Dan Tunjangan Kerja Terhadap Kinerja ASN Di UPT Perpustakaan Proklamator Bung Karno - Kurniawan, Nanang Yudhi; Evasari, Aprilia Dian (Universitas Islam Kadiri, 2024)
The performance of each employee is different from other employees according to their level of knowledge, skills, and motivation. Human resource management carried out professionally can improve employee performance. The aim of this research is to determine the significance of the influence of motivation, work environment, and work benefits on performance. The data research techniques in this research are Questionnaire/Questionnaire techniques, Observation, and Documentation Techniques. Data Quality Test using Validity and Reliability Test. Data analysis techniques use Multiple Linear Regression Analysis, F Test, and T Test. Based on the results of statistical analysis, it can be explained that the influence of motivation on performance has a sig value. 0.011<0.05. The influence of work environment variables on performance has a value of sig.0.011 <0.05. The influence of the work allowance variable on performance has a sig value. 0.001> 0.05. From these results, it can be concluded that the variables of motivation, incentives, and work environment have a significant influence on performance at the UPT Proklamator Bung Karno Library.